«Місяць світе – мертвець їде. Чи боїшся, дівко?»: міжнародний сюжет ATU 365 (наречений‑мрець) в українському фольклорному наративі - Демедюк, Марина (Slavia Orientalis, 2026)
The article provides a comprehensive analysis of the international fairy tale plot ATU 365 ‘The Dead Bridegroom’ within the Ukrainian oral storytelling tradition. The study is based on a wide range of sources from the 19th to the early 21st century, including classic folklore publications, archival records, and field materials from various ethnographic regions of Ukraine. The focus is on the interaction between the fairy tale and the demonological legend, which determines the specific plot dynamics of the texts and the change in semantics. The author traces the development of the narrative sequence from the longing for a deceased lover, the return of the dead groom, and a joint journey – to the finale, which can end in either the heroine’s rescue or her death. Particular attention is paid to the motifs of excessive mourning and the violation of funeral taboos, which, according to popular beliefs, open the way between the world of the living and the dead. It is demonstrated that the image of the dead returning for the living in Ukrainian tradition tends towards the demonological type of the ‘restless dead’ and vampire‑like creatures. The article identifies the most common mechanisms of rescuing the heroine: from apotropaic actions to ritual stopping of time (rooster crowing), which reflect deep‑seated beliefs about the necessity of bringing the dead to their proper ontological status. The genre hybridity of Ukrainian variants of ATU 365 is emphasised, in which fairy‑tale models coexist with folk beliefs about the dangers of contact with the underworld. Thus, the plot of ‘The Dead Bridegroom’ is interpreted as a narrative mechanism for regulating the emotional experience of loss, which supports culturally significant norms of dealing with the deceased and establishes the irreversibility of death in the traditional worldview.